Regulation of externalities: rights, options, and procedure - Schläpfer, Felix; Vatn, Arild (Frontiers in Environmental Economics, 2023)
When governments regulate externalities, they inevitably create, modify or reassign property rights. Although these rights have important distributional implications, they are rarely at the center of economic evaluations of policy instrument choice, where the main focus is on allocative efficiency. This is problematic for two reasons. First, the allocation of rights may not receive the attention it deserves, and decisions about rights and more technical policy advice are easily mixed up. The second reason is a circularity problem: proposed (Pareto) efficient regulations modify the same property rights that determine what economists identify as an efficient environmental target. To avoid these difficulties, we propose a perspective in regulation that brings the allocation of rights to the front. We classify basic regulatory options based on how rights are allocated between polluters and potential victims and across income groups and we outline how these options may be implemented through choice of policy instruments. We then propose a regulatory procedure that takes the interdependence of rights and environmental targets into account. Based on this analysis, we discuss the potential of a rights-centered approach for designing environmental policies with desirable distributional outcomes and assumptions about the rights to environmental resources.